Intoxication before intercourse and risky sexual behavior in male veterans with and without human immunodeficiency virus infection. - Cook, Robert L; McGinnis, Kathleen A; Kraemer, Kevin L; Gordon, Adam J; Conigliaro, Joseph; Maisto, Stephen A; Samet, Jeffrey H; Crystal, Stephen; Rimland, David; Bryant, Kendall J; Braithwaite, R Scott; Justice, Amy C (Medical care, 2006)
Male veterans represent a large population at risk for acquiring or transmitting human immunodeficiency virus (HIV) infection. We sought to determine the prevalence of risky sexual behavior among veterans with and without HIV infection and to assess the relationship of intoxication before intercourse and other measures of drug and alcohol use to risky sexual behavior in this population.
Keywords: Cohort Studies; Coitus; HIV Seropositivity; Humans; Male; Middle Aged; Poisoning; Questionnaires; Risk-Taking; Veterans